Nitrogen Preferences during Alcoholic Fermentation of Different Non-Saccharomyces Yeasts of Oenological Interest - Roca-Mesa, Helena (Microorganisms, 2020)
Non-Saccharomyces yeasts have long been considered spoilage microorganisms. Currently, oenological interest in those species is increasing, mostly due to their positive contribution to wine quality. In this work, the fermentative capacity and nitrogen consumption of several non-Saccharomyces wine yeast (Torulaspora delbrueckii, Lachancea thermotolerans, Starmerella bacillaris, Hanseniaspora uvarum, and Metschnikowia pulcherrima) were analyzed. For this purpose, synthetic must with three different nitrogen compositions was used: a mixture of amino acids and ammonium, only organic or inorganic nitrogen. The fermentation kinetics, nitrogen consumption, and yeast growth were measured over time. Our results showed that the good fermentative strains, T. delbrueckii and L. thermotolerans, had high similarities with Saccharomyces cerevisiae in terms of growth, fermentation profile, and nitrogen assimilation preferences, although L. thermotolerans presented an impaired behavior when only amino acids or ammonia were used, being strain-specific. M. pulcherrima was the non-Saccharomyces strain least affected by the nitrogen composition of the medium. The other two poor fermentative strains, H. uvarum and S. bacillaris, behaved similarly regarding amino acid uptake, which occurred earlier than that of the good fermentative species in the absence of ammonia. The results obtained in single non-Saccharomyces fermentations highlighted the importance of controlling nitrogen requirements of the wine yeasts, mainly in sequential fermentations, in order to manage a proper nitrogen supplementation, when needed.